2017
DOI: 10.1088/1741-4326/aa5e36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resonant magnetic perturbations on fast ion prompt loss in tokamaks

Abstract: Fast ion prompt loss induced by resonant magnetic perturbations (RMPs) is simulated by solving Hamiltonian equations strictly in the guiding center coordinate system. Full orbit simulations show that the prompt loss rate can increase significantly in resonant regions when RMPs are added. Furthermore, the prompt loss rate is larger in the low-field side than in the high-field side in tokamak plasmas. Detailed analyses show that a number of trapped ions which lie near the center of the trapped region can be lost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The role played by the special banana orbits in transport has been studied theoretically [39,40] for energetic ions, where the orbits are referred to as superbanana orbits and the related transport is of great importance for predicting the performance of thermonuclear fusion reactors. This kind of banana orbit has also been demonstrated for a ITER-like equilibrium recently [41]. Due to the relatively high-q equilibrium here, unperturbed orbits with zero precession frequency are very close to the trapped-passing boundary in phase space.…”
Section: Losses Enhanced By Stochastic Banana Orbits Under N = 1 Rmpsupporting
confidence: 68%
See 1 more Smart Citation
“…The role played by the special banana orbits in transport has been studied theoretically [39,40] for energetic ions, where the orbits are referred to as superbanana orbits and the related transport is of great importance for predicting the performance of thermonuclear fusion reactors. This kind of banana orbit has also been demonstrated for a ITER-like equilibrium recently [41]. Due to the relatively high-q equilibrium here, unperturbed orbits with zero precession frequency are very close to the trapped-passing boundary in phase space.…”
Section: Losses Enhanced By Stochastic Banana Orbits Under N = 1 Rmpsupporting
confidence: 68%
“…With the n = 1 RMP applied, these particles, instead of wobbling in a limited range of ζ as shown previously in an ITER-like equilibrium [40], experience transitions between the passing and trapped orbits. This is no surprise because the orbits are so close to the trapped-passing boundary and RMP can trigger the conversions of orbit types [41]. It is interesting to note that the precession rate is still negligibly small when the orbits are in trapped state, which means that the resonance is still possible and helps to explain the large radial excursions shown in figure 15(b).…”
Section: Losses Enhanced By Stochastic Banana Orbits Under N = 1 Rmpmentioning
confidence: 87%
“…Unravelling the physics behind the mechanisms leading to fast-ion transport induced by externally applied 3D fields has been the subject of many numerical and theoretical studies in the past years [16,18,27,[29][30][31][32][33][34][35][36]. However, it is a challenging task since it is a multidimensional problem dealing with the interaction of, in general, 5D FI distribution functions (three spatial coordinates, plus the energy and pitch angle of the particles) with 3D magnetic field topologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of 3D magnetic field perturbations enhances the fast ion transport and loss, as observed in KSTAR, ASDEX-Upgrade, DIII-D, and MAST [13][14][15][16]. Several simulation studies have investigated the fast ion loss induced by 3D magnetic perturbations, and they indicate that enhanced fast ion loss will occur under an externally applied 3D field [16][17][18][19][20][21][22][23][24]. Other studies [17][18][19] have also revealed that resonant interactions between the fast ions and the 3D field break the conservation of toroidal canonical angular momentum and increase fast ion transport.…”
Section: Introductionmentioning
confidence: 99%